Tradition and its significance within Islam and the Abrahamic faiths - Ghani, Usman (2022)
The present article looks into the position and significance of tradition within Islam and the Abrahamic Faiths. Tradition in its very theological sense is generally believed to have divine authority albeit not as part of the sacred scripture. The main interest here is to shed light on how different tradition in Islam in comparison to Judaism and Christianity is. Drawn upon examples and evidence, this article thus, studies the idea of tradition and underlines its notional and applied similarities and differences within the said three world religions. Further, this article also investigates and discusses the intricacies of the Islamic tradition.